The Utilization of Educational Intelligence Technology Applications In Higher Educational Institutions In Sarawak - Hamrila, Abdul Latip (Universiti Malaysia Sarawak, (UNIMAS), 2007)
This paper aims to investigate the utilization level of educational intelligence applications among lecturers from the Engineering and Business faculties of higher educational institutions in Sarawak, Malaysia. In this study, the utilization of educational intelligence applications was tested by One-way ANOVA, which is used to compare the utilization level of educational intelligence applications among lecturers between the two aforementioned faculties. The major findings reveal that the utilization level of educational intelligence applications was low despite the fact that all higher educational institutions were well equipped with educational technologies and facilities. Results of the analysis disclosed the utilization of educational intelligence applications in public higher educational institutions was higher than private institutions. The result also indicated that the utilization of educational intelligence applications in engineering faculties was higher than in business, in both public and private institutions. The Spearman’s Rho correlation analysis is also done to determine the relationship between philosophical factor and the utilization of educational intelligence technology applications. The hypothesis of a relationship between the dependent variable, that is utilization of the educational intelligence applications with the philosophical factor was designed based from few studies previously done by Fox (1998), Myatt (1999), Kirkman, Osorio and Sachs (2002), and Tinio (2002). The correlation result showed that the philosophical factor had a low, positive relationship with the utilization of educational intelligence applications. It can be concluded that the low utilization level of the available educational technologies can be explained by the lecturer’s philosophical elements. Therefore, this study can be viewed as groundwork in providing justification for the level of utilization of educational technologies in Malaysian higher educational institutions.